Research proposal on architectural copper-based antimicrobic solutions in high traffic spaces. Issue 8 (1st November 2022) - Ferraro, C; Esposito, M A
Abstract: This contribution investigates research opportunities in the field of architecture and design management focusing on user health in high traffic spaces. The field of application is Airport Passenger Terminals. Looking at the COVID-19 pandemic and anticipating the possibility of events of the same magnitude, it is necessary to approach the problem of the safety in public spaces. Based on the State of the Art about antimicrobial material studies, Science of Architecture could propose innovative solutions that are compliant with health safety and prevention for high-use surfaces. These solutions will combine antimicrobial materials with a digital solution that could manage data about surfaces, allowing the maintenance team to valuate and optimize operations. After few hours the hygiene level of copper-based surfaces is higher than any other material. Copper-based furniture could be paired with sensors that send data to management software. Combining the use of scientifically demonstrated antibacterial surfaces with high-performance management tools could be the best option to achieve health safety and contribute to social sustainability. Airport terminals are the ideal high-traffic buildings to use as test model because they have all the characteristics that could be analysed concerning the safety and the perception of safety of architectural spaces by users.